Effects of Human Resource Management Practices on Organizational Performance: A Study in ENAMC as a Public Manufacturing Company in Algeria - Oussama, Saoula (2012)
This study investigates the effects of Human Resource Management practices on organizational performance, which include practices such as recruitment and selection process, training and development practice, compensation and benefits system and performance appraisal system and are treated as independent variables. The study was conducted in public manufacturing company in Algeria ENAMC. The data was collected and analyzed objectively from a total of 130 responses; examined if Human Resource Management practices have significant effects on organizational performance. The aim is to get a clear and actual picture of the effects of Human Resource Management practices on organizational performance. The finding indicates that, there are positive effects of Human Resource Management practices on organizational performance. This study is important for several reasons. Firstly, recognizing positive effects between, HRM and organizational performance; secondly, to clarify the problems and barriers encountered in the application of human resource programs in Algerian companies in the context of the case included in this study. Thirdly, to participate in and contribute to research, resulting in Knowledge increase, and lastly, to assist scholars and other researchers in the HRM field.